Implementasi nilai-nilai anti korupsi dalam membangun integritas generasi muda di indonesia - aldiyansyah, mohammad satrio (Maliki Interdisciplinary Journal, 2026)
Corruption continues to be one of the major challenges encountered by Indonesia because it has the potential to obstruct national development, generate financial losses for the state, and diminish public confidence in governmental and public institutions. In this context, the younger generation holds an essential role as agents of change in fostering a culture that upholds honesty, responsibility, discipline, and integrity. This study aims to examine the implementation of anti-corruption values in strengthening the integrity of the younger generation in Indonesia. The research method employed is a literature review through the analysis of journals, books, scientific articles, and several sources obtained from the UIN Malang repository related to character education and anti-corruption education. The findings indicate that the application of anti-corruption values can be carried out within family, school, university, community, and digital media environments. Furthermore, the success of anti-corruption education among young people is strongly influenced by the roles of educators, parents, and society. The consistent implementation of anti-corruption education is capable of developing young individuals who are honest, disciplined, responsible, and possess strong moral awareness in social, national, and civic life. Therefore, strengthening anti-corruption values is expected to produce a generation with strong integrity and a firm commitment to preventing corruption in Indonesia.